In Vitro Corneal Permeation of Etoricoxib from Oil Drops - Acharya, Ajit Kumar (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Topical administration of drugs is the most favored route for management of ocular inflammation as it provides higher ocular drug concentrations, keeping away the systemic side effects associated with the oral administration. In vitro transcorneal permeation of etoricoxib from oil, drops were studied using freshly excised goat cornea. Materials and Methods: Based on solubility of etoricoxib in several oils, formulations were well prepared (0.5% w/v in arachis, castor, mustard, olive, and sesame and 1.0% w/v in arachis, castor, and sesame oil) with or without benzyl alcohol (0.5% v/v) as a preservative. Permeation studies were conducted using all-glass modified Franz diffusion cell, and the drug permeation in receptor was measured by spectrophotometer at 234 nm, after 120 min. Results and Discussion: Raising drug concentration from 0.5% to 1.0% w/v increased permeation. The maximum corneal permeation was obtained with 1.0% (w/v) etoricoxib drops in sesame oil with benzyl alcohol, while minimum from 0.5% (w/v) formulation in castor oil without benzyl alcohol. Corneal hydration obtained with all the formulations were between 75% and 80% indicating no corneal damage except in castor oil with benzyl alcohol. The saturation solubility of etoricoxib in sesame oil at 4Â°C is 1.128% (w/v). Conclusion: Etoricoxib 1.0% (w/v) drops in sesame oil containing 0.5% (v/v) and benzyl alcohol showed maximum permeation (0.057 mg or 0.553%).